Evaluation of a new NS1 rapid diagnostic test using a single acute‐phase serum panel collected during the largest dengue outbreak in Taiwan history in 2015. Issue 4 (21st December 2021) - Liu, Li‐Teh; Chen, Chun‐Hong; Lin, Ping‐Chang; Tsai, Ching‐Yi; Hsu, Miao‐Chen; Huang, Bo‐Yi; Tsai, Yan‐Yi; Tsai, Jih‐Jin
Abstract: Dengue virus (DENV) infection results mostly from the bites of virus‐carrying Aedes mosquitoes, which results in dengue fever (DF) with or without warning signs, severe dengue, or asymptomatic infections in humans. For point‐of care identification of DENV‐infected patients, a rapid diagnostic test (RDT) for DENV nonstructural protein 1 (NS1) has been developed to achieve early diagnosis and timely clinical management. We evaluated the performance of a new commercially available dengue NS1 RDT AsiaGen Dengue NS1 Antigen Rapid Diagnosis Test using real‐time qRT‐PCR as a reference method and compared the results with SD BIOLINE Dengue NS1 Ag using a single acute‐phase serum panel collected during the largest dengue outbreak in the history of Taiwan in 2015. The results suggested that the sensitivity and specificity of AsiaGen Dengue NS1 Antigen RDT (96.9% and 100%) were similar to those of SD BIOLINE Dengue NS1 RDT (100% and 100%) for detection in the acute phase of DENV‐2 infection. The results suggested that the sensitivity of both RDTs was similar (95.4% 100%) for the sera collected at less than or equal to three days postsymptom onset (PSO). Our results suggested that the two DENV NS1 RDTs used in this study were promising for the timely diagnosis of DENV infection during dengue outbreaks, at least for DENV‐2 in areas where authorized medical laboratories are not available or medical resources are limited. However, the performance of AsiaGen DENV NS1 RDTs in the detection of primary/secondary infections and infection by serotypes of DENV other than DENV‐2 requires further investigation.